A concepção de linguagem na prova de redação do vestibular da Universidade Federal do Espírito Santo no período de 2000 a 2010 - Oliveira, Ana Paula Gomes de (2012)
The objective is to investigate the concepts of language, text, writing and subject which have been underlying the writing exams used in the entrance examinations (" vestibular ) for Universidade Federal do Espírito Santo UFES. In order to do so, the research pursues the answers to the following questions: a) Which concepts of language, text, writing and subject which have been underlying the writing exams for the entrance examinations for UFES? b) Do the concepts which have been underlying the writing exams for the entrance examinations for UFES dialog with the theoretical tendencies which pervade the production of knowledge in the linguistics and education fields and that have been present in the official syllabi for mother tongue teaching for Elementary and High schools? c) Do the assessment criteria used by the board of correctors reflect such tendencies? Theoretically, this investigation anchors itself, mostly, to the contributions of Bakhtin (2003, 2006) and other authors such as Marcuschi (2007, 2008), Geraldi (1996, 1997, 2003, 2006), Travaglia (1991,1996), Koch (2003) e Koch e Elias (2006), which approach different dimensions of language, writing, subject and text. The methodology employed is the documental analysis, using as a corpus the exams for the entrance examinations for UFES in the period between 2000 and 2010. The exam analyses reveal that the views on the writing exam, concerning the studied period, have shown changes which cover a moment in which the exam privileged eminently school writing practices, supported by a conception of language as a representation of thought, and writing as a way of expressing thought, to another moment in which there was an approaching between the textual genres and the social practices of the subject, in an exam model based upon the use of language in interactional conditions. The criteria present in the correction grid of the writing exams for UFES also express the language conceptions adopted along those periods, fact which corroborates the results accomplished through the analyses of the exams proposed by the university